Trafficking in Cure and Harm: Placebos, Nocebos and the Curative Imaginary - Berkhout, Suze G.; Jaarsma, Ada S. (Disability Studies Quarterly, 2018)
This article tracks the traffic of placebos, nocebos and the effects or meaning-responses that they solicit in order to contribute to wide-ranging critiques of the curative imaginary. Moving through three realms of biomedicine (the clinic, the lab and the market), the article explores key contradictions at play within biomedicine that become more recognizable through attentiveness to placebos and nocebos. In order to make this case, the article forges a conversation between Feminist Science Studies, Disability Studies and a counter-strand in Placebo Studies. What emerges is an understanding of placebos and nocebos that foregrounds the biosocial dynamics and always-entwined relations between cures and harm.